Vascular brain accident and cerebral dominance in people living at high altitude - Romero Córdova, José Antonio (2019)
Objective. To determine the clinical-epidemiological characteristics of stroke and the dominant hemisphere in people living at high altitude. Method. A descriptive, prospective, cross-sectional study was conducted from april to july 2016. 28(100%) patients with stroke diagnosed by imaging tests were included. Results. 19 patients (67.8 %) were women and 24 (85.7 %) were over 60 years old. 15 (53.5 %) had ischemic stroke and 13 (47.5%) had hemorrhagic stroke. the factors associated with the stroke were: age over 60 years old, low socioeconomic level, high blood pressure and being a  woman. in 20 patients (71.4 %) the right hemisphere was involved, while in 8 patients (28.6 %) the left hemisphere was involved. in almost half of the patients the anatomical location was in the basal ganglia (42.9 %). right-handed manual preference was found in 75%, followed by ambidextrous manual preference (25%). Conclusions. It is concluded that the right cerebral hemisphere, not being dominant, was the most affected; being found more frequent of right-handed compared to ambidextrous, in a relation of 3:1. however, the frequency of ambidextrous people was higher at high altitude than at sea level.